2019
DOI: 10.29173/istl2
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Systematic Review Publication Trends in Conservation Biology Journals

Abstract: Researchers in conservation biology and other non-medical fields are adopting systematic review as a research methodology. Since this methodology requires extensive and well-documented literature searching, it is beneficial for information professionals to understand disciplinary developments in its use. This article investigates trends in systematic review publication in conservation biology journals between 1998 and 2017 and examines the prevalence of search reporting among these systematic reviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Other papers did not share a full search strategy. These poor search methods are consistent with observations from other studies of systematic reviews that found authors only searched one database [8] or used poor quality searches [16], [17] . In particular, "many published systematic reviews have been found to contain errors in the design and conduct of the searches that could affect their quality" [18, p. 2] .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Other papers did not share a full search strategy. These poor search methods are consistent with observations from other studies of systematic reviews that found authors only searched one database [8] or used poor quality searches [16], [17] . In particular, "many published systematic reviews have been found to contain errors in the design and conduct of the searches that could affect their quality" [18, p. 2] .…”
Section: Discussionsupporting
confidence: 88%
“…Two other disciplines we were interested in examining were software engineering and environmental sciences or environmental engineering. These areas are of interest as there is existing research about systematic reviews conservation biology [8] and software engineering [14] . Boice [8] demonstrated that systematic reviews have become more common in conservation biology, so we would predict that related engineering disciplines would also adopt systematic review methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The key words "citizen science" and "biodiversity monitoring" were used to search Web of Science. This database was chosen due to its common use in systematic reviews, specifically surrounding biodiversity conservation research, and the large number of results generated in the initial search (Boice, 2019). Results were initially filtered to include only journal article submissions before 2022.…”
Section: Selection Of Studiesmentioning
confidence: 99%